The influence of leadership, teacher commitment, and organizational culture through the independent learning curriculum on improving education quality - Rejaan, Silvius; Rokhman, Fathur; Yanto, Heri; Wasino, Wasino (Edelweiss Applied Science and Technology, 2025)
This study aims to analyze the influence of school principal leadership, teacher commitment, and organizational culture on improving education quality by implementing the independent learning curriculum in Southeast Maluku Regency senior high schools/vocational schools. The study employed a quantitative approach using a survey method with 250 respondents, comprising 230 teachers and 20 school principals, analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results indicated that school leadership and organizational culture positively and significantly influenced the implementation of the Merdeka Belajar curriculum, while teacher commitment did not show a significant influence. Furthermore, implementing the Merdeka Belajar curriculum was found to have a positive and significant impact on improving educational quality. These findings highlight the importance of strengthening the role of school principals and developing an organizational culture that supports the successful implementation of the Merdeka Belajar curriculum to enhance educational quality.